Aqueous hydrazine borane N2H4BH3 and nickel-based catalyst: An effective couple for the release of hydrogen in near-ambient conditions. Issue 6 (December 2018) - Kahri, Hamza; Flaud, Valérie; Ridha, Touati; Demirci, Umit B.
Abstract: Nickel-based bimetallic catalysts were screened using the sodium borohydride NaBH4 hydrolysis and the aqueous hydrazine borane N2 H4 BH3 dehydrogenation. A total of 22 bimetallic catalysts were synthesized according to an easy process while focusing on metals like Fe, Co, Ni, Cu, Rh, Pd, Ag, Ir, Pt and Au. In the end, the bimetallic candidate Ni87.5 Pt12.5 showed to be the most active and the most selective for the dehydrogenation of N2 H4 BH3 . At 70 °C, it is able to decompose N2 H4 BH3 into 5.8 equivalents of H2 +N2 in less than 12 min such as: N2 H4 BH3  + 3H2 O → 0.95 N2  + 0.1 NH3  + B(OH)3  + 4.85H2 . Durability and stability tests were also performed. In our conditions, Ni87.5 Pt12.5 was found to suffer from small loss of performance because of an electronic evolution of the catalytic surface leading to modified sorption properties of the catalytic sites. Our main results are reported and discussed herein. Highlights: Easy preparation of efficient nickel-based bimetallic catalysts is reported. 22 nickel-based bimetallic catalysts were screened for NaBH4 hydrolysis. They were then screened for dehydrogenation of aqueous N2 H4 BH3 . The bimetallic candidate Ni87.5 Pt12.5 showed to be the most active and selective. At 70 °C, it decomposes N2 H4 BH3 into 5.8 equivalents of H2  + N2 in <12 min.